Respuesta :

Answer:

[tex]x^2y^2+x^4=2[/tex]

Step-by-step explanation:

The given differential equation is:

[tex]2x^2+y^2+xyy'=0,x\:>\:0,y(1)=1[/tex]

We rewrite this as

[tex]2x^2+y^2+xy\frac{dy}{dx}=0,x\:>\:0,y(1)=1[/tex]

We make [tex]\frac{dy}{dx}[/tex] the subject to get:

[tex]\frac{dy}{dx}=\frac{-2x^2-y^2}{xy}[/tex]....a homogeneous equation.

[tex]\frac{dy}{dx}=-2(\frac{x}{y})-(\frac{y}{x})[/tex]

We use the following substitutions to obtain a seperable equation:

[tex]y=vx,\frac{dy}{dx}=v+x\frac{dv}{dx},v=\frac{y}{x},\:and\:\frac{1}{v}=\frac{x}{y}[/tex].

This implies that:

[tex]v+\frac{xdv}{dx}=\frac{-2}{v}-v[/tex]

[tex]\frac{xdv}{dx}=\frac{-2}{v}-2v[/tex]

[tex]\frac{xdv}{dx}=\frac{-2-2v^2}{v}[/tex]

[tex]\frac{v}{-2-2v^2}dv=\frac{dx}{x}[/tex]

We integrate both sides to obtain:

[tex]\int \frac{v}{-2-2v^2}dv=\int \frac{dx}{x}[/tex]

[tex]\frac{-\ln|2v^2+2|}{4}=\ln x+\ln K[/tex]

[tex]-\ln|2v^2+2|=4(\ln x+\ln K)[/tex]

[tex]\ln (\frac{1}{2v^2+2})=4\ln (Kx)[/tex]

[tex]\ln (\frac{1}{2v^2+2})=\ln(K^4x^4)[/tex]

[tex]\frac{1}{2v^2+2}=Cx^4[/tex]

[tex]Cx^4(2v^2+2)=1[/tex]

We substitute [tex]v^2=\frac{y^2}{x^2}[/tex] to get:

[tex]Cx^4(2*\frac{y^2}{x^2}+2)=1[/tex]

We substitute x=1,y=1 from the initial conditions.

[tex]C(1)^4(2*\frac{1^2}{1^2}+2)=1[/tex]

[tex]4C=1[/tex]

[tex]C=\frac{1}{4}[/tex]

Our solution now becomes:

[tex]x^2(2y^2+2x^2)=4[/tex]

[tex]x^2(y^2+x^2)=2[/tex]

[tex]x^2y^2+x^4=2[/tex]